Rehabilitation support system using shapetapeTM sensor - Fatin Umiayu, Nasaruddin (2016)
Nowadays, there are many rehabilitation support systems are proposed. Rehabilitation is a process of recovering human body to normal condition after an illness, injury or disease. This process requires continuous monitoring in order to provide the results. However, the existing rehabilitation support system has its own shortage. Firstly, the system needs fully supervised by specialist during the rehabilitation process. Secondly, patients lack of feedback about the effect of their rehabilitation process in real time. Lastly, the existing system have no offline data logging capabilities. The primary objective in this project is to monitor and analyze the movements behavior during rehabilitation process. The secondary objective is to evaluate the data movements in real-time and used the offline data for further analysis. The ShapeTapeTM sensor will be use as input device in this project to collect the data movements. The Shape Recorder software will provide the visual feedback on the PC before stored the data gained from the sensor in the offline system for deep analysis by specialist. In this project, rehabilitation support system will be focus on the human hand and leg.